Estimating average inpatient and outpatient costs and childhood pneumonia and diarrhoea treatment costs in an urban health centre in Zambia - Chola, Lumbwe (BioMed Central, 2009)
BACKGROUND: Millions of children die every year in developing countries, from preventable diseases such as pneumonia and diarrhoea, owing to low levels of investment in child health. Investment efforts are hampered by a general lack of adequate information that is necessary for priority setting in this sector. This paper measures the health system costs of providing inpatient and outpatient services, and also the costs associated with treating pneumonia and diarrhoea in under-five children at a health centre in Zambia. METHODS: Annual economic and financial cost data were collected in 2005-2006. Data were summarized in a Microsoft excel spreadsheet to obtain total department costs and average disease treatment costs. RESULTS: The total annual cost of operating the health centre was US$1,731,661 of which US$1 284 306 and US$447,355 were patient care and overhead departments costs, respectively. The average cost of providing out-patient services was US$3 per visit, while the cost of in-patient treatment was US$18 per bed day. The cost of providing dental services was highest at US$20 per visit, and the cost of VCT services was lowest, with US$1 per visit. The cost per out-patient visit for under-five pneumonia was US$48, while the cost per bed day was US$215. The cost per outpatient visit attributed to under-five diarrhoea was US$26, and the cost per bed day was US$78. CONCLUSION: In the face of insufficient data, a cost analysis exercise is a difficult but feasible undertaking. The study findings are useful and applicable in similar settings, and can be used in cost effectiveness analyses of health interventions.